Determinants of paddy farmers unsustainability farm practices - Mohamed, Zainal Abidin; Terano, Rika; Sharifuddin, Juwaidah; Rezai, Golnaz (Elsevier, 2016)
Sustainable agriculture is closely related to farming practices. In order to attain sustainable agriculture, there are many farming practices such as land preparation, used of fertilizers and weedicides among other indicators of farming practices. In particular, weed and pest control are focal points for certain crops such as cotton, rice, vegetables, and fruit with heavily applied chemical inputs which cause unsustainability in farming. Among food crops, paddy requires heavy doses of fertilizers, weedicides and pesticides to keep it healthy and productive. The objective of this study is to determine the factors that contribute to unsustainability of paddy farming practices at field level via Paddy Farmer Sustainability Index (PFSI) based on the current 33 paddy farming practices. Tobit regression analysis found that knowledge and awareness have played important role in determinant of unsustainability level in paddy farming.